Perencanaan Kebutuhan Sumber Daya Manusia dalam Peningkatan Kualitas Manajemen SDM Pendidikan: Systematic Literature Review - Imeldania, Pranisma Salsa; Isdaryanti, Barokah; Sutarto, Joko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human resource (HR) needs planning is a strategic aspect in improving the quality of educational HR management. The availability of competent teaching and administrative staff needs to be supported through a systematic planning process so that educational institutions can achieve their goals effectively and sustainably. This study aims to analyze the role of HR needs planning in improving the quality of HR management in educational institutions. The research method used is a Systematic Literature Review (SLR) with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Research data was obtained by searching scientific articles in the Google Scholar database with a publication range of 2022–2026 using keywords related to educational HR planning, HR management, and improving the quality of education. Articles that met the inclusion criteria were analyzed using thematic analysis techniques to identify patterns and key findings. The results of the review of 20 articles indicate that HR needs planning plays a crucial role in improving the quality of educational management through workforce needs analysis, competency-based recruitment and placement, professional development, performance management, and the implementation of a culture of continuous quality improvement. However, the implementation of human resource planning still faces various obstacles, such as budget constraints, teacher administrative burdens, digital competency gaps, and suboptimal performance evaluation systems. Therefore, educational institutions need to implement adaptive, targeted, and sustainable human resource planning strategies that address future competency needs to produce professional educators and support improvements in education quality.